Percepções docentes sobre o ensino de ciências e a educação do campo em escolas do município de Toledo/Pr - Kliemann, Claudia Regina Machado (2017)
In the early years of the century XXI, the Brazilian formal education offered to the populations of rural areas has been reformulated and re-signified. A new modality of Basic Education was structured, Rural Education, which is regulated at the national level, manly by Operational Guidelines of the Rural Education (BRASIL, 2001a) and in the state level by the Curricular Guidelines of the Rural Education (PARANÁ, 2006), in which intended schools in the countryside offering an Rural Education. Science education provides meaningful, historical and contextualized teaching to students (KRASILCHIK, 2000) and these concerns are also considered to be the basis for Rural Education. Thus, the science teaching of the rural schools should be presented in a dialogical, in which the established problematizations are contextualized with the reality of the students, disturbing their prior knowledge, articulating the concepts and establishing the scientific knowledge. As a guide to the process, the teacher guides the way of the dialogical process of teaching science in the rural schools. In this way, this research has the objective of characterizing the Rural Education and the teaching of Sciences in this context, by verifying the perceptions of the science teachers in the rural state schools of the city of Toledo/PR. Twelve Sciences teachers of the rural state schools of Toledo/PR and two technicians of the Regional Education Center of this city took part in the research. The instrument of data collection was an individual interview from a semistructured questionnaire. The statements provided in the interviews were analyzed through the technique of Content Analysis, as formulated by the french thinker Laurence Bardin (1977). The results show that teachers know little about the Rural Education legislation and the respective basic documents, the rural schools are characterized as particular spaces because of the context in which they are inserted, and therefore also, the teachers seek to assume a differentiated pedagogical practice with the aim of bringing curricular contents closer to students' reality. There is also the perception that the continuing education offered by the Regional Education Center hasn‟t address the theme to date. The considerable turnover of teachers was evident, which is pointed out as one of the factors that makes it more difficult to know the students' reality. Thus, internal character of actions in schools and other linked to the State Department of Education must be coordinated to enable the realization of Rural Education in rural schools.